2019
DOI: 10.1093/jisesa/iez122
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mitogenomic Analysis of the Eurydema Genus in the Context of Representative Pentatomidae (Hemiptera: Heteroptera) Taxa

Abstract: The family Pentatomidae, the largest within the superfamily Pentatomoidae, comprises about 5,000 species; many of which are economically important pests. Although the phylogeny of Pentatomidae species has been studied using various molecular markers, their phylogenetic relationships remain controversial. Recently, mitochondrial genomes (mitogenomes) have been extensively employed to examine the phylogenetics and evolution of different insects, and in this study, we sequenced complete/near-complete mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
7
15
0
Order By: Relevance
“…Compared to the varied size of complete mitogenomes, relatively little variation was observed in the length of PCGs, tRNAs, and rRNAs. This is consistent with previous Pentatomidae mitochondrial genomic studies [ 41 , 43 ]. Similarly, the AT content of Pentatomidae species was significantly higher the GC content [ 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Compared to the varied size of complete mitogenomes, relatively little variation was observed in the length of PCGs, tRNAs, and rRNAs. This is consistent with previous Pentatomidae mitochondrial genomic studies [ 41 , 43 ]. Similarly, the AT content of Pentatomidae species was significantly higher the GC content [ 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous Pentatomidae mitochondrial genomic studies [ 41 , 43 ]. Similarly, the AT content of Pentatomidae species was significantly higher the GC content [ 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…From the PCG-NT or PCG-AA datasets, the heterogeneity of most pairwise comparisons was low with site score above 0.5. The low heterogeneity of pairwise comparisons demonstrated that the two datasets were applicable for further phylogenetic studies [60].…”
Section: Variations Genetic Distance and Evolution Rates Of Pcgsmentioning
confidence: 99%